2015
DOI: 10.1002/adhm.201500740
|View full text |Cite
|
Sign up to set email alerts
|

3D Micropillars Guide the Mechanobiology of Human Induced Pluripotent Stem Cell‐Derived Cardiomyocytes

Abstract: 3D micropillars generated by photolithography are used as a platform to probe by atomic force microscopy the mechanodynamics of human induced pluripotent stem cell-derived cardiomyocytes. 3D micropillars guide subcellular cytoskeletal modifications of cardiomyocytes and lead to biochemical changes altering beating rate, stiffness, and calcium dynamics of the cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Consequently, Young's modulus of hiPSC-CMs is expected to be lower than that of primary cells. In fact, according to AFM-based measurements, the average apparent Young's modulus for adherent hiPSC-CMs has been reported to be between 0.3 kPa and 0.5 kPa [41,42]. Likewise, from our RT-DC measurements we derive an average Young's modulus for individual hiPSC-CMs of 1.25 ± 0.08 kPa.…”
Section: Discussionsupporting
confidence: 62%
“…Consequently, Young's modulus of hiPSC-CMs is expected to be lower than that of primary cells. In fact, according to AFM-based measurements, the average apparent Young's modulus for adherent hiPSC-CMs has been reported to be between 0.3 kPa and 0.5 kPa [41,42]. Likewise, from our RT-DC measurements we derive an average Young's modulus for individual hiPSC-CMs of 1.25 ± 0.08 kPa.…”
Section: Discussionsupporting
confidence: 62%
“…This technique can provide a quantitative force map of cardiomyocytes exerted to each pillar, offering a powerful tool for cardiac contractility studies with a high spatial resolution at the singlecell level. [120,122] Currently, most MPAs are made of PDMS substrate using soft lithography techniques. To enable cardiomyocytes to adhere to the tips of the micropillars, MPAs were functionalized with extracellular matrix protein.…”
Section: Micropillar Arrays (Mpas)mentioning
confidence: 99%
“…In recent years, a different method using the micropillar/micropost arrays (MPAs) has been utilized for measuring the contractile force of smooth muscle cells, [ 116,117 ] endothelial cells, [ 118 ] neural stem cells, [ 119 ] and cardiomyocytes. [ 120,121 ] This system relies on the array of compliant micropillars with constant controllable dimensions (diameter and height), and the contractions of attached cells bend the micropillars, whose deflections are observed by optical microscopy. Then the contractile forces exerted by cells can be calculated from the displacements of micropillars using beam bending theory.…”
Section: Contractile Force Detectionmentioning
confidence: 99%
“…Another approach to improve MEA microfabrication would be to create a substrate that integrates topography that can guide network formation and can simultaneously stimulate neuronal maturation. A number of studies have demonstrated the ability of topography to direct cell growth, control cell shape and polarity, and affect differentiation and proliferation [7][8][9]. In general, the response to topography depends on the substrate and the specific surface features that are being introduced and even more on the cell type under examination.…”
Section: Introductionmentioning
confidence: 99%